SIFAT ANATOMI DAN FISIS KAYU JATI DARI MUNA DAN KENDARI SELATAN - Sri Rulliaty; Mody Lempang (Pusat Penelitian dan Pengembangan Hasil Hutan, 2004)
It is traditionally acknowledged that teak wood (Tectona grandis L.f) originated from Muna district had a better quality than that of South-Kendari. The objective of this study was to evaluate the different characteristics of both teaks. Wood samples were collected from bottom, central and top part of trees from age class 11 and Ill (18 and 28 years) extracted from each region. Samples were then examined for their anatomical and physical characteristics to determine the quality.Results revealed that teak wood samplesfrom Muna had higher dimensions in fiber diameter,fiber lumen width and vessel diameter than those of South-Kendari samples. Such characteristics might bring the samples from Muna to have a higher specific gravity than the South-Kendari samples. It was also clearly shown that the older trees (age class III) possessed better characteristics than those of the young ones (age class II).